Ценности и их роль в формировании и функционировании профессиональной культуры личности - Вейсова, В.Э. (Культура народов Причерноморья, 2013)
В статье обосновывается роль ценностей в структуре и содержании профессиональной
культуры личности, излагается авторское толкование ценностей профессиональной деятельности.
Показано, что ценности профессиональной деятельности выступают в качестве призмы, сквозь
которую преломляются требования к работнику в силу соответствующей специфики его профессии.
Эта специфика выражается в системе знаний, умений, навыков, способностей, а также в
дополнительных требованиях к его социально-нравственному развитию, не являющихся эквивалентами
требований общих, так и в иной расстановке социально-нравственных ориентаций в сознании индивида
деятельности. У статті обгрунтовується роль цінностей у структурі та змісті професійної культури
особистості, викладається авторське тлумачення цінностей професійної діяльності. Показано, що
цінності професійної діяльності виступають в якості призми, крізь яку переломлюються вимоги до
працівника чинності відповідної специфіки його професії. Ця специфіка виражається в системі знань,
умінь, навичок, здібностей, а також у додаткових вимогах до його соціально - моральному розвитку ,
які не є еквівалентами вимог загальних, так і в іншій розстановці соціально-моральних орієнтацій у
свідомості індивіда діяльності. The article explains the role of values in the structure and content of the professional culture of the
individual, the author sets out the interpretation of the values of professional activity. It is shown that the values
of professional activity act as a prism through which to refract the requirements to the employee by virtue of the
relevant specifics of his profession. This specificity is reflected in the system of knowledge, skills, abilities, as
well as additional requirements to its social and moral development , is not equivalent to the requirements of the
general, and in particular the balance of social and moral orientations in the mind of the individual activities.
Formulated the following functions in the system of values of professional culture: the motivation, orientation,
regulatory, tool , integration , compensatory , control . The conclusions of the article noted that the
transformation of Ukrainian social system actualizes the problem of harmonization in the individual employee's
professionalism and values, values consistent with the aims and objectives of the progress of society , sociocultural
development of the individual .